Pengaruh Variasi Bentuk Adsorben Karbon Aktif dan Scale-up Kolom Terhadap Kinerja Adsorpsi CO2 Dalam Biogas - Suprianti, Yanti; Pangestu, Yoga Rahmat; Iriani, Purwadi (Jurnal Energi Dan Manufaktur; Vol 15 No 1 (2022)DO - 10.24843/JEM.2022.v015.i01.p04, 2023)
Biogas as a renewable energy source is now starting to be considered as an alternative energy to replace BBM and CNG. Biogas from cow dung generally has a concentration of 50-70% CH4 as a substance that can be used as fuel, accompanied by 25-50% CO2, 0.3-3% N2, 1-5% H2, and H2S. The presence of accompanying substances, especially CO2, which has no calorific value (cannot be burned), can reduce the overall calorific value of biogas. One way to separate the CO2 gas is by adsorption. However, at a small column capacity, the adsorbent is often saturated quickly after being operated for a certain time. One way to get around this is to make the adsorbent into a more compact form, such as pellets. By combining granular and pellet activated carbon, this study wanted to identify the effect of variations to produce the best biogas composition and compare its performance when scaled up. The results showed that mixture A (70% granular activated carbon and 30% pellet) produced the best biogas, namely 83.1% in the initial column and 89.3% in the scale up column, with CO2 impurities removed and a small amount of other gases. The absorption performance in the form of adsorption effectiveness showed that each variation showed 100% effectiveness. The breakthrough curve shows that mixture C (30% granular activated carbon and 70% pellet) gave the highest resistance for 7 minutes on the initial column and 10 minutes on the scale up column. The volume of biogas that was adsorbed, the volume of biogas/column height, and the total amount of remove solute were best indicated by mixture A with 72 Liters, 180 Liters/m, and 8,208 Liters in the initial column, and 159 Liters, 212 Liters/m, respectively. and 21,942 Liters in the scale up column. Scale up has a significant impact on the performance of mixed C adsorbent with an increase in the volume of biogas that is adsorbed by 2.75x, the volume/height of the column increases by 1.47x, and the total of remove solute by 3.29x. Keywords: adsorption, adsorbent, granular activated carbon, pellet, scale up